Taking charge of adult ADHD - Barkley, Russell A., 1949- 4 0 16; Benton, Christine M.; 5 (New York : The Guilford Press, 2010)
Offers information and advice to adults who have been diagnosed or think they may have attention deficit disorder, discussing medications, rules for success, tips on mastering ADHD in specific areas of life, and stories from others who have the disorder.
Includes bibliographical references and index.
Adult.
Keywords: 2 -- 0; 6; Attention-deficit disorder in adults;Attention deficit disorder. -- Popular works; 20; 2